2018
DOI: 10.1038/s41598-018-32513-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide discovery of DNA polymorphisms by whole genome sequencing differentiates weedy and cultivated rice

Abstract: Analyzing the genome level DNA polymorphisms between weedy and cultivated rice is crucial to elucidate the molecular basis of weedy and agronomic traits, which in turn can enhance our ability to control weedy rice and its utilization for rice improvement. Here, we presented the genome-wide genetic variations between a weedy rice accession PSRR-1 and two cultivated rice accessions, Bengal and Nona Bokra, belonging to japonica and indica subspecies, respectively. The total number of SNPs and InDels in PSRR/Benga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 76 publications
4
19
1
Order By: Relevance
“…With an in-depth analysis of the potential polymorphisms responsible for filled grain number under salt stress of flowering rice, the annotation of polymorphisms observed in MY/KK-JK/NN revealed that only ~3% of SNPs and ~2% of InDels were detected in CDSs, whereas the remaining ~35% of SNPs and ~36% of InDels were detected in upstream regions (Figure 4C,D). The larger number of variations in regulatory regions other than genic regions found in this study corresponds to the results of previous studies in rice [74,75]. We identified 722 high-impact variants resulting in changes such as frameshifts, exon loss and stop loss and 5120 moderate-impact variants, such as missense variants (non-synonymous) (Table S4).…”
Section: Discussionsupporting
confidence: 87%
“…With an in-depth analysis of the potential polymorphisms responsible for filled grain number under salt stress of flowering rice, the annotation of polymorphisms observed in MY/KK-JK/NN revealed that only ~3% of SNPs and ~2% of InDels were detected in CDSs, whereas the remaining ~35% of SNPs and ~36% of InDels were detected in upstream regions (Figure 4C,D). The larger number of variations in regulatory regions other than genic regions found in this study corresponds to the results of previous studies in rice [74,75]. We identified 722 high-impact variants resulting in changes such as frameshifts, exon loss and stop loss and 5120 moderate-impact variants, such as missense variants (non-synonymous) (Table S4).…”
Section: Discussionsupporting
confidence: 87%
“…A higher ratio is an indicator of good quality SNPs as sequencing errors and false positive variants have a ratio closer to one [28].We found SNP transitions (A/G and C/T) are the most common substitution in the genome, which is consistent with other crop species like foxtail millet (Setaria italica) [29], tea (Camellia sinensis) [30], soybean [31], rice [22]. We observed a Ts/Tv ratio of 1.71 is however less than the ratios reported in crops like rice [22], maize (Zea mays) [32] and tea [30]. The higher Ts/Tv could be because of more synonymous mutations resulting due to transitions than transversions, which brings out the change in protein structure and function.…”
Section: Discussionsupporting
confidence: 81%
“…Despite having uniform genome coverage of mapped reads several empty bins were identified because of the stringent variant calling parameters used as indicated in the methods section. Such significant differential distribution of DNA polymorphisms has also been reported in Arabidopsis and rice [20][21][22].…”
Section: Discussionsupporting
confidence: 55%
“…Dular is a lowland drought tolerant cultivar with deep roots [63]; Nona Bokra and Pokkali are salt tolerant land races [64,65]. PSRR-1 is a weedy rice genotype from Louisiana [66] and is closely related to indica subspecies [67].…”
Section: Plant Materials and Cultivationmentioning
confidence: 99%